The Effect Of Incentive, Technology Readiness, And Charging Infrastructure On Electric Vehicle Adoption Mediated By Perceived Behavior Control (Empirical Study: Intention To Adopt Electric Vehicles In Jakarta And Its Surroundings) - Wiejaya, Hendra; Gularso, Kurnadi (Al-Makki Publisher, 2024)
Today, the world faces crucial challenges such as the energy crisis, air pollution, and greenhouse gas emissions. The transportation sector is considered a major contributor to these problems, which is driving climate change in various cities. To achieve the goal of zero emissions, electric vehicles are positioned as the transportation solution of the future and need to be widely adopted around the world. This researche focuses on analyzing the factors that affect the intention to adopt electric vehicles, with variables such as Incentive, Charging Infrastructure, Technology Readiness, Perceived Behavior Control, and intention to adopt. The goal is to understand how these factors contribute to shaping people's decisions to use electric vehicles. This study uses a quantitative approach with a sample of at least 150 respondents. Data collection was carried out through an online questionnaire, and data analysis was carried out using the structural equation modeling (SEM) method with Smart-PLS (Partial Least Squares Structural Equations Modeling) software version 3.0 Testing of validity, reliability, and goodness of fit was carried out to ensure the quality of the model.